Host satisfaction towards short term rental accommodation (STRA) regulation in stratified property: a case study of airbnb in I-City, Shah Alam / Abu Asyad Abdul Halim and Thuraiya Mohd - Abdul Halim, Abu Asyad; Mohd, Thuraiya (2023)
Short Term Rental Accommodation (STRA) activity is where homeowners rent their residential properties for a short term of stay on digital platforms such as Airbnb. However, there is absence of regulation on federal level to govern STRA activity. Hence, this research aimed to explore host satisfaction towards Airbnb regulatory aspect in and embarks on the objectives which are to identify scopes of rules imposed on Airbnb activities in stratified property, to identify existing rules imposed on Airbnb activities I-City, and to investigate host satisfaction on existing rules imposed. A mixed method research design was applied where both qualitative and quantitative approach were involved. Data was collected through literature review, a semi-structured interview with Facility Manager of i-City JMB, and questionnaire survey to Airbnb host in i-City. The data from both interview and questionnaire survey was analysed descriptively with application of SPSS software and presented in table form. Finding from interview indicate that Airbnb operation in i-City is not subjected to exclusive by-laws pertaining to Airbnb operation but rather regulated by different set of general house rules that relates with Airbnb operation. Survey finding showed that facility usage rules have the highest satisfaction from Airbnb hosts in i-City, which followed by permission rules in the 2nd rank, nuisance control rules at the 3rd, and host eligibility rules at the 4th rank. Meanwhile, building safety rules show the most dissatisfaction due to one specific rule regarding prohibition of mailbox as self-check in method.